SYSTEMATIC LITERATURE REVIEW: IMPLEMENTASI PENDEKATAN STEM (MANFAAT DAN TANTANGAN) DI INDONESIA - Fika Ariani Thovawira; Islamiani Safitri; Supartik Supartik; Nova Nadila Saputri Sitompul; Ikke Anggriyani (STKIP Andi Matappa, 2020)
To face the challenges of today's education requires skills such as thinking skills, analytical skills, and also skills in creativity. Education with the approach of science, technology, engineering and mathematics (STEM) is a problem in the world of education in Indonesia today. The implementation of the STEM approach that is carried out in learning activities motivates students to be able to manage and carry out integrity through technology, as well as apply knowledge in everyday life. The purpose of this study was to determine the implementation of the STEM approach (benefits and challenges) in Indonesia using the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate, and interpret all available research on the topic area of the phenomenon of interest, with specific relevant research questions. The use of the SLR method can systematically identify journals, which in each process follow predetermined steps or protocols. The number of articles found was 56 articles with the characteristics according to the research target, then through the screening process 30 articles were taken, after that the next stage was the exclusion criteria for exclusion so that 25 articles were found for further review. The results showed that the implementation of the STEM approach in Indonesia had a fairly good effect on the creative thinking of students, student worksheets, student books and facing the industrial revolution 4.0, mathematical literacy and STEM implementation with robotics, as well as teachers' perceptions of STEM learning